DIAGNOSIS KESULITAN BELAJAR DAN FAKTOR PENYEBABNYA PADA PELAJARAN EKONOMI KELAS XI MAS RAUDHATUL ULUM - Puspitasari, Ria; Matsum, Junaidi H; Khosmas, Khosmas (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe purpose of the study is to know which students are experiencing learning difficulties and to know the internal and external factors that cause learning difficulties. This research is a qualitative descriptive study aimed at describing and analyzing the phenomenon. Data obtained in the form of primary and secondary data and sourced from researchers as key insrtrumen, economics teachers, class XI students and other documents. In collecting data used observation techniques, interviews, documentation as well as tests and analyzed through the process of redukation, data presentation process, and the withdrawal process conclusion. The results showed that almost all students have difficulty learning economics from 50 people there are 43 students who have difficulty learning. If viewed from the material that is learned by the difficulties that students are involved in all materials studied in the even semester. While the internal factors that cause students to have difficulty learning are poor learning attitudes, lack of motivation to learn and bad learning habits.  As for external faktot cause learning difficulties because his teacher only use one method that is lecture method. In addition to that, the availability of limited learning facilities makes learning objectives not achieved with its presets.Keywords: Diagnosis, difficulty learning and factors cause